Approaches and methods used in long-term social planning and policy-making: conclusions of the Seminar at Arc-et-Senans, France (3-10 May 1972) and collection of working papers submitted to the Seminar - United Nations (New York : United Nations, 1973)
This collection is based on the documentation assembled for a Seminar on Methods Used in Long-Term Social Planning and Policy-Making, which was held at Arc-et-Senans (France) from 3 to 10 May 1972 in pursuance of a decision by the E/ECE/ECON.ADVICERS/2, paragraph 50(b)
"United Nations publication. Sales no. E.73.II.E.7."
At head of title: Economic Commission for Europe.
Includes bibliographical references.
osc 12/12/2018
Loans
Keywords: Social planning; System analysis; Social indicators